2012
DOI: 10.1080/03601277.2011.645424
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Goal Concordance, Time Use, and Well-Being

Abstract: The primary purpose of the present study was to investigate age differences in goal concordance, time use, and Well-Being. Past research has found that despite age-related decline in life circumstances (e.g., health), the Well-Being of older adults is as high as young adults. The present study used a novel approach to explore the Paradox of Well-Being. One hundred and seventy-seven adults participated in the study. They first generated their three most important personal strivings and rated levels of goal conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…This research emphasizes the underlying purpose and meaning of an activity in contrast to the specific characteristics of the activity itself (e.g., physical vs. social) 12 . Research on motivation has shown that, as individuals age, they increasingly prioritize relationships and activities that they consider meaningful, including increased interest in spirituality/religiosity as well as in activities such as volunteering 13, 14 In contrast, younger adults may be more motivated by novel experiences 13-15 . If this is so, then leisure activities with higher potential for deeper meaning may constitute a useful category to focus on when examining the relation between leisure activities and cognitive function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research emphasizes the underlying purpose and meaning of an activity in contrast to the specific characteristics of the activity itself (e.g., physical vs. social) 12 . Research on motivation has shown that, as individuals age, they increasingly prioritize relationships and activities that they consider meaningful, including increased interest in spirituality/religiosity as well as in activities such as volunteering 13, 14 In contrast, younger adults may be more motivated by novel experiences 13-15 . If this is so, then leisure activities with higher potential for deeper meaning may constitute a useful category to focus on when examining the relation between leisure activities and cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In contrast, younger adults may be more motivated by novel experiences. [13][14][15] If so, then leisure activities with higher potential for deeper meaning may constitute a useful category to focus on when examining the relationship between leisure activities and cognitive function. Research showing that similar activities were associated with higher cognitive function only when they were performed as part of leisure and not when they were part of work indirectly supports this idea.…”
mentioning
confidence: 99%
“…Depuis ce temps, les recherches empiriques et théoriques dans le domaine de la motivation ont démontré que l'engagement dans un but personnel intrinsèque (p. ex., affiliation, apprentissage, croissance personnelle) prédit le BEP (Chen, Lee, Pethtel, Gutowitz et Kirk, 2012;Dubé, Lapierre, Bouffard et Alain, 2007;Klug et Maier, 2014;Riediger, Freund et Baltes, 2005;Sheldon, 2014;Sheldon et al, 2010;Wiese, 2007). Ainsi, les gens peuvent gagner un bonheur durable et vivre des expériences stimulantes en se fixant de nouveaux buts et en faisant des efforts pour les réaliser plutôt que d'attendre que les circonstances de la vie améliorent leur situation (Sheldon et Lyubomirsky, 2006 Chez les personnes âgées, la présence de projets est aussi associée au BEP (Lapierre, Bouffard et Bastin, 1993.…”
Section: Introductionunclassified
“…Le déclin physique et les bouleversements qui l'accompagnent suggèrent un possible impact négatif sur le bonheur des personnes âgées. Pourtant, il semble que la majorité d'entre elles arrivent à maintenir une attitude positive face à leur vie, malgré la présence de ces contraintes et difficultés, en priorisant des buts émotionnellement gratifiants qui favorisent le BEP, comme de développer un réseau de relations interpersonnelles sélectives enrichissantes, plutôt que des objectifs à long terme comme le succès (Carstensen, 2011;Chen et al, 2012). Il semble que les aînés heureux choisissent des buts qui correspondent davantage à leurs intérêts et à leurs valeurs personnelles (Chen et al, 2012;Sheldon et Elliot, 1999).…”
Section: Introductionunclassified
“…Research suggests that older adults, including older students, report more desire to pursue work-related activities and less desire to pursue sleep than younger adults, or younger students (Chen, Lee, Pethel, Gutowitz, & Kirk, 2012). The desire to pursue work-related activities most likely translates to more time spent pursuing work-related activities.…”
Section: Time Management Theorymentioning
confidence: 99%